PENGARUH SISTEM INFORMASI AKUNTANSI (SIA), GAYA KEPEMIMPINAN, KECERDASAN EMOSIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. BANK SUMUT - Alifhia, Yulia; Lubis, Sahat Agustian; Sitorus, Jessy Safitri; Sanjaya, Ni Made Wulan Sari (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the influence of accounting information systems, leadership style, emotional intelligence, and job satisfaction on employee performance. The population for this study consists of employees at PT. Bank Sumut Headquarters in Medan, with a total of 80 participants relevant to the variables under investigation; the sampling process was determined using the saturation sampling method. A quantitative approach was chosen as the method for this study, and the analysis utilized multiple linear regression. The simultaneous test revealed that all independent variables had a significant impact on the dependent variable. However, when examined partially, AIS and leadership style were not found to be significant in influencing performance. Conversely, emotional intelligence and job satisfaction were found to be significant in influencing performance. The study results indicate that individual personality traits have a stronger impact on employee performance. Therefore, efforts to improve performance should focus more on employee training and self-development.